Causes of delay in the building construction industry in major cities of Iran - Kouchaknezhad, Mehran (2011)
The problem of delays in the construction industry is a global issue and it affects construction projects in Iran. This thesis presents the results of a study that was undertaken to determine and evaluate the importance of different factors causing delays in the building construction in major cities of Iran. The survey covered 90 selected factors causing delays which were grouped into four major categories, namely owner related, consultant related, contractor related, and external related. The main reasons for the delays were analyzed and ranked according to the different categories using different analyses. It was found that owners and consultants believe that contractors were the most important party in creating delay in the building construction industry in Iran, while contractors believe that consultants and owners were the important parties in creating delays. This study identified ten most important causes of delays from a list comprising 90 pre-determined causes. The ten most important causes were: lack of experience among the subcontractors, inadequate contractor‟s work, low productivity and efficiency of equipment, insufficient numbers of equipment, deficiencies in planning and scheduling, frequent equipment breakdown, poor quality, poor construction methods, financial difficulties and equipment allocation problems which were all put together in the contractor category. These factors were the main causes of delays in the building construction in major cities of Iran, and they could provide a basis for developing strategies to minimize delays in construction projects.